(untitled) (Malaysian Journal of Civil Engineering, 2018)
The concepts of eco-friendly building are getting more attention today. The use of materials from natural sources is an alternative to the realization of the green building concept. Considering this approach, a study was conducted to investigate the potential of cockle shell ash as a material for partial cement replacement or a filler material. The study was to determine the chemical composition of cockle shell ash and were determined using Fluorescence X-ray analysis. The observation of on the morphology structure based on SEM analysis was also performed. The next phase involved in determining the concrete properties such as compressive strength, tensile, modulus of elasticity, water permeability and porosity made from mixture of cockle shell ash of 5%, 10%, 15%, 25%, 50% and compared to normal concrete cured in ordinary water at the 7, 28, 90 days and up to 120 days for water permeability test. As a result, with the inclusion of 5% and 10% of cockle shell ash, morphology structure seems compacted that effected the strength, modulus of elasticity, permeability and porosity of the concrete.